Kaposiform hemangioendothelioma with Kasabach-Merritt phenomenon in a neonate - role of dual therapy: A case report and review of literature - Gaurav Parashar; Gowri Shankar; Ravindra Sahadev; Ramesh Santhanakrishnan (Wolters Kluwer Medknow Publications, 2020)
Kaposiform hemangioendothelioma (KHE) represents a rare, borderline vascular tumor with locally aggressive behavior. They are often associated with a potentially life-threatening coagulopathy known as Kasabach-Merritt phenomenon (KMP). Due to heterogeneous nature of the vascular lesion and lack of standardized treatment protocols, these patients pose a diagnostic dilemma and therapeutic challenge with morbidity and potential mortality. We report successful management of an infant with KHE and associated KMP. Difficulties encountered in diagnosis, initiation of therapy, and role of dual therapy with vincristine and steroids are discussed.